Mobile Health Care in Developing Countries: A Narrative Review - Haeruddin Haeruddin; Reza Aril Ahri; Rezky Aulia Yusuf (International Journal of Artificial Intelligence Research, 2022)
This paper aims to synthesize the literature on mobile healthcare in developing countries. We employed a narrative review methodology to describe mobile healthcare in developing countries narratively. Two health and information technology research databases were searched for papers covering this domain. Two reviewers assessed the articles. Articles were then synthesized via narrative review. Mobile healthcare holds tremendous potential for transforming healthcare delivery in developing countries. By leveraging mobile technologies, mHealth interventions can improve access to healthcare, enhance disease prevention and management, and empower community health workers. Sustainable strategies that involve collaborations among stakeholders are necessary to overcome these obstacles and ensure the long-term effectiveness of mHealth solutions in improving health outcomes for underserved populations. Mobile technology has the power to fundamentally alter how healthcare is provided in underdeveloped countries. MHealth initiatives may use mobile technology to reduce barriers to access, improve health outcomes, and let individuals take an active role in their own healthcare. Through persistent research, cooperation, and innovation, the Sustainable Development Goal of ensuring healthy lives and well-being for everyone might be significantly advanced by mobile healthcare.